THE INVOLVEMENT OF THE COMPLEMENT SYSTEM IN THE PROCESSES IN ATHEROGENESIS - Librandi, Ana Paula Landi; Pandochi, Ana Isabel Assis (Medicina (Ribeirao Preto), 2008)
Atherosclerosis has been considered a chronic inflammatory illness induced by macrophage activation, T lymphocyte and complement system. This system corresponds to a group of plasma and membrane proteins, which are activated by a cascade of interactions that result in the production of some pro-inflammatory molecules. Although it is one of the effector mechanisms of the innate immune system, in certain circumstances, the system complement can itself contribute for "triggering" cardiovascular diseases. This review contains a brief description of the complement cascade and the processes of atherogenesis as well as the involvement of immunological factors, mainly the complement system activation on patogenesis of atherosclerosis.